Zirconium in the Nuclear Industry: Ninth International Symposium 1991
DOI: 10.1520/stp25519s
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Growth Mechanism on Zirconium Alloys

Abstract: In order to get a better understanding of the mechanisms governing corrosion of Zr-based alloys, several examinations have been performed on a variety of samples with uniform and nodular corrosion and different oxide layer thicknesses. The results point to a barrier layer concept. The oxide layer becomes porous at a critical thickness. Open porosity increases from 0.01% at 10 μm to 3% at 100 μm. Between the outer porous oxide and the metal, a dense interlayer exists. This is only ≤30 nm in nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 6 publications
3
41
1
Order By: Relevance
“…These range from the accumulation of stresses giving rise to cracks in the oxide [12], the formation of defects such as microcracks and interlinking nano-pores [18,19], changes in the conductivity of the oxide layer [4], and transformation from the tetragonal to the monoclinic phase. This phase transformation has been associated with increasingly compressive stresses in the monoclinic phase at the point of transition [5], with cracking in the oxide [2], and with the linking-up of nano-porosity [15] thereby aiding the transport of the environment to the metal-oxide interface [1,15,20,21]. Pêcheur et al [22] associated the accelerated corrosion rate to the gradual transformation of the tetragonal phase to the monoclinic phase in the protective 'barrier layer'.…”
Section: Introductionmentioning
confidence: 99%
“…These range from the accumulation of stresses giving rise to cracks in the oxide [12], the formation of defects such as microcracks and interlinking nano-pores [18,19], changes in the conductivity of the oxide layer [4], and transformation from the tetragonal to the monoclinic phase. This phase transformation has been associated with increasingly compressive stresses in the monoclinic phase at the point of transition [5], with cracking in the oxide [2], and with the linking-up of nano-porosity [15] thereby aiding the transport of the environment to the metal-oxide interface [1,15,20,21]. Pêcheur et al [22] associated the accelerated corrosion rate to the gradual transformation of the tetragonal phase to the monoclinic phase in the protective 'barrier layer'.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the SEM micrographs of our samples (Fig.6), the oxide layer appears to be homogeneous (excepted a few cracks). Nevertheless, it has been found by impedance spectroscopy [10,27] that the oxide layer grown on ZrNbO could be divided into two sub-layers. For the kinetic modelling, two possibilities can be imagined, involving one or two oxide layers: -either one oxide layer with micropores and diffusion of adsorbed species via this porosity, -or two oxide layers: the microporous layer and a very thin and dense layer near the metal/oxide interface (for example, the native oxide layer), in which the diffusion of oxygen vacancies is very rapid.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen deficient zirconia near the metal interface seems to play an important role in maneuvering high compressive stress in oxide generated during oxidation [13]. Hart and Chaklader found that oxygen-deficient zirconia has superplasticity at a high temperature and that tetragonalmonoclinic inversion is not destructive in oxygen-deficient pure zirconia [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stability of the tetragonal phase is highly very dependent on the factors in the surrounding environment such as compressive stress, grain size and surface energy [13]. Oxygen vacancy is observed to be important in maintaining the stability of tetragonal zirconia.…”
Section: Discussionmentioning
confidence: 99%